2017
DOI: 10.1177/0031512517736463
|View full text |Cite
|
Sign up to set email alerts
|

Equine Exercise in Younger and Older Adults: Simulated Versus Real Horseback Riding

Abstract: Horseback riding is an effective exercise for improving postural control and balance. To reduce costs and improve accessibility, simulated horseback riding has been developed; but no differential effects of simulated and real horseback riding on muscle activation patterns in older adults have been studied. Thus, we compared muscle activation patterns for older and younger adults engaged in real and simulated horseback riding exercises, using surface electromyography recordings of the erector spinae, rectus abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…All studies with conditions that controlled for movement or rhythm were included in this category. They included rhythm and music-based therapy (e.g., Bunketorp Kall et al, 2012 ) or the vibrations or movements of a mechanic horse (Cho, 2017 ; Funakoshi et al, 2018 ; Kim et al, 2018 ). We found that 5.81% ( n = 10) of the studies controlled for rhythm or movement as a non-specific factor.…”
Section: Resultsmentioning
confidence: 99%
“…All studies with conditions that controlled for movement or rhythm were included in this category. They included rhythm and music-based therapy (e.g., Bunketorp Kall et al, 2012 ) or the vibrations or movements of a mechanic horse (Cho, 2017 ; Funakoshi et al, 2018 ; Kim et al, 2018 ). We found that 5.81% ( n = 10) of the studies controlled for rhythm or movement as a non-specific factor.…”
Section: Resultsmentioning
confidence: 99%
“…The trunk muscles, particularly the rectus abdominis, have been demonstrated to coordinate their activation to the horse’s movement [ 55 ], which coordinates body segments for posture [ 30 ]. The internal oblique helps to control posture by increasing intraabdominal pressure, which is aided by the rectus abdominis and transverse abdominis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The internal oblique helps to control posture by increasing intraabdominal pressure, which is aided by the rectus abdominis and transverse abdominis [ 56 ]. Terada et al [ 55 ] reported that the horse riding elicited a greater adductor muscle activity, and its rectus abdominis activation uses the hip flexion to control the posture [ 30 ], which explains the greater improvement of pelvis posture of the experimental group. Furthermore, horseback riding alters muscle use and joint motions, perhaps leading to increased adductor muscle activity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in favor of the HRS, it generates between 50 and 100 three-dimensional physical movements (forward and back, left and right, up and down) [32]. Some examples of HRS devices are JOBA [32], OSIM uGallop, Taiwan [30], Fortis [33], S-RIDER Shinwha Electron [34], Honjin, Korea [25], and Model H-702 [35], HJLCo. Ltd., Seoul Korea [31].…”
Section: Instructionmentioning
confidence: 99%